Possibility study of implementing vertical constructed wetland for domestic waste water treatment in urban kampong - Haryati Sutanto; Paulus Bawole (Universitas Gadjah Mada, 2021)
The Indonesian Ministry of Environment in 2014 released study results that 60-70% of rivers in Indonesia have been polluted by domestic wastewater, which is not treated properly. Improper and inadequate wastewater treatment not only pollutes water resources and damages ecosystems, but can also pose a significant public health risk. The development of spontaneous settlements in urban kampong makes the environmental quality within the settlements getting worse and many people consider that the area of urban kampong is not habitable. The efforts to treat wastewater before being discharged into water bodies are very important. The study of